A eficácia da fonoforese no alivio da dor e melhora da função na osteoartrite de joelho: uma revisão de escopo - Moraes, Jean Carlos Rodrigues (Brasil, 2021)
Objective: Check whether phonophoresis is effective in relieving pain and improving function in knee osteoarthritis, as well as seeking the parameters / drugs used in it. Methods: The databases used to search for articles were: PubMed, Virtual Health Library, SciELO, PEDro, CAPES - Brazil Theses and Dissertations Catalog, Abstracts of Brazilian Journals and Brazilian Digital Library of Tests and Dissertations, published in the period between February 2011 to March 2021. Results: After the searches, 7 articles were included in this review, which show positive results of phonophoresis in the impacts of knee osteoarthritis. Conclusion: Phonophoresis is effective in relieving pain and improving function in individuals with knee osteoarthritis.